2008
DOI: 10.1093/ajcn/87.2.449
|View full text |Cite
|
Sign up to set email alerts
|

n–3 Fatty acid erythrocyte membrane content, APOE ε4, and cognitive variation: an observational follow-up study in late adulthood

Abstract: These data are evidence of a gene x environment interaction for cognitive aging. They are relevant to the analysis of trials of n-3 PUFA supplements in cognitive aging and dementia prevention, and they support heterogeneity in cognitive aging and, possibly, in Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 27 publications
10
100
0
1
Order By: Relevance
“…GC coupled with FID has previously been used to determine serum FFA levels [14,21,22]. Although this method is highly sensitive, its dependability is questionable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GC coupled with FID has previously been used to determine serum FFA levels [14,21,22]. Although this method is highly sensitive, its dependability is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid profiles of erythrocyte membranes can be affected by plasma FFAs [35]. Higher erythrocyte n-3 PUFA contents have been suggested to be associated with higher cognitive scores; however, this difference was only significant in the absence of the APOE İ4 allele [14]. Further studies addressing the possible relationship between AD and the fatty acids of human erythrocyte membranes should be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both have found that the risk of dementia was decreased by 40% by regular fish consumption only in APOE4 non-carriers while no association was observed in APOE4 carriers. The two following studies (Beydoun et al, 2007;Whalley et al, 2008) have considered the relationship between blood concentrations of EPA and DHA and cognitive decline. Similarly, both have observed a significantly lower decline with higher proportions of EPA and DHA only in APOE4 non-carriers.…”
Section: Interactions Between Lc N-pufa and Apoe4 On Cognitionmentioning
confidence: 99%
“…Whalley et al [91,92] conducted an observational study of 350 mentally efficient subjects born in 1936 whose mental ability was tested in 1947 and who were followed up to in 2000/01, at which point cognition, supplement use, diet, and risk factors for vascular disease were assessed. This investigation showed that use of food supplements in late adulthood can influence cognitive performance.…”
Section: Nutrients and Cognitive Functionmentioning
confidence: 99%